PEMBERDAYAAN MASYARAKAT MELALUI KELOMPOK SWABANTU DALAM MENGELOLA SAMPAH MENJADI APE ANAK USIA DINI - KURNIAWAN ERMAN WICAKSONO ERMAN (Media Husada Journal Of Nursing Science, 2020)
Waste in the most common problem in the world, not only in developin countries but also in developed countries. Waste has always been a major problem. Good knowledge of waste management followed by the attitude of parent’s who support waste management as an educational game tool is one ay to solve the waste problem. Community empoerment activities in managing waste are very helpful in overcoming waste volume accumulation. Knowing the effect of community empowerment through self-help groups on the knowledge and attitudes of parents in waste management becomes an Educational Game Tool. The study used a pre-experimental design with one group pre-test and postest approaches given to 24 respondent. The level of knowledge and attitudes in managing waste into an educational game was obtained by e questionnaire. The statistical test used Wilcoxon. The results of the bivariate analysis obtained p=0.002 which showed that there is an effect of community empowerment through self-help groups on the knowledge and attitudes of parents in processing waste into educational games. This study shows that before the waste management extension intervention was carried, 3 respondents were categorized as sufficient in attitude. And after being given the intervention, 24 respondent got a god category in knowledge, and 21 respondent were in a good category in attitude. Counseling on waste management (recycling) should be carried out regularly to assist the community in reducing waste accumulation, knowledge and attitudes in managing waste